How expressing one's likes and dislikes affects enjoyment: a replication - Julia Sophia Wittich; Jan R. Landwehr; Daniel Wentzel (Marketing Letters, 2023)
A recent article by He, Melumad, and Pham (Journal of Consumer Research 46(3):545–563, 4 ) showed that consumers experienced greater enjoyment when they were asked to perform an evaluative task relative to a non-evaluative task. In this research, we intend to replicate this finding and to examine to what extent the strength of the effect is contingent on the sample employed. Using a sample from Amazon MTurk, study 1 replicates the indirect effect but not the total experimental effect. Study 2 draws on a sample that is unacquainted with the experimental paradigm and replicates the indirect as well as the total experimental effect. These findings suggest that the sampling population of MTurk may have become desensitized to the basic experimental paradigm.
Keywords: 380; Liking; Self-expression; Replication